Tensile splitting response of steel fibre reinforced concrete - Lu, Gang. (2008)
In this thesis, details of the modified SHPB and the design of a novel striker bar are highlighted. Numerical simulation and practical dynamic tensile splitting tests were conducted. Dynamic tensile splitting strength, response history and the crack propagation behavior have been determined.